Localização dos barorreceptores no tambaqui, Colossoma macropomum (Teleostei: Serrasalminae) - Armelin, Vinicius Araújo (2015)
The cardiovascular system plays the fundamental role of supplying the needs of the animals bodily tissues. It both provides the cells with a variety of elements that are essential to their functioning and drains potentially harmful substances, such as metabolites. All of these items are transported through the blood, the propulsion of which is determined by the pressure gradient created by the heart. In addition to promoting circulation, blood pressure is also directly involved in the maintenance of many other physiological processes, making the preservation of this variable at satisfactory levels a prerequisite for an organism s vitality. In light of this need for ideal pressure levels, important mechanisms for blood pressure regulation have been selected during the evolutionary history of vertebrates, and the baroreflex serves as a clear example. These reflexes begin with the monitoring of arterial pressure by baroreceptors, which constantly inform the central nervous system (CNS) of the condition of this variable. The CNS is thus able to change heart rate and systemic vascular resistance in order to normalize arterial pressure when necessary. Though the operation of the baroreflex is already widely understood and though baroreceptors have been located in mammals, these issues are not elucidated and remain quite controversial when it comes to fishes. Thus, the objective of this work was to locate the baroreceptors and their afferences in a teleost, the Colossoma macropomum. To do so, the occurrence and efficiency of the baroreflex were analyzed when this mechanism was induced by pressure imbalancements in intact fish (IN), fish with the first pair of gill arches denervated (G1) and fish with all four pairs of gill arches denervated (G4). The pressure imbalancements were promoted by the administration of the α1-adrenergic agonist phenylephrine and the α1-adrenergic antagonist prazosin, and the baroreflex was assessed using an electrocardiogram that measured heart rate (bpm), relation between pre- and post-pharmacological manipulation heart rates (%), the time required to reach maximum chronotropic baroreflex response, and total heart rate variability (ms). The results revealed that the barostatic reflex was attenuated in the G1 group and nonexistent in G4 group indicating that baroreceptors may be exclusively located in the gill arches of teleosts.